Analyzing the Legislative Prescriptions Representing Persons with Disabilities in South Africa - Gcabashe, Sazi; Pillay, Sareesha; Teyise, Nangamso (Technium Social Sciences Journal, 2022)
The legislative prescriptions promoting and protecting the rights of disabled people in South Africa are some of the most comprehensive globally. These prescriptions are applied across all the spheres of government to eliminate the discrimination faced by persons with disabilities. This study analyzed selected legislation and public policies representing persons with disabilities in the country with reference to the City of Cape Town. The study sought to identify features of the government’s efforts to improve the lives and participation of disabled people and to better implement inclusive legislation and policies. Through a desktop analysis, the study found that legislation and governmental policies that protect and promote the rights of persons with disabilities provide a framework from which disabled people can exercise their economic, political, and social rights as equal members of the citizenry. However, the state of disability in relation to policy and legislation does pose challenges to the effectiveness of these prescriptions to eliminate discrimination and promote equality. The study recommends the strengthening of legislation and policies through strategies that involve the partnerships of government and civil society. There is also a need to review the existing legislative framework to identify and eliminate barriers that limit the equality of disabled people.